2022
DOI: 10.3390/disabilities2030036
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stroke on the Quality of Life (QOL) of Stroke Survivors in the Southeast (SE) Communities of Nigeria: A Qualitative Study

Abstract: Purpose: This study aims to explore the Quality of Life (QOL) amongst ten stroke survivors in the SE communities of Nigeria. Design: Qualitative study using semi-structured interviews. Interpretative phenomenological analysis (IPA) was utilized. Setting: Medical institutes in the southeast communities of Nigeria. Participants: 10 participants ranging in age from 29 to 72 years old. Stroke is typically a life-changing catastrophe, claiming over 55 million lives and disabling 44 million people each year. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The result of this study also revealed that majority of the stroke cases seen at the neurology clinic of physiotherapy department UPTH were male 208 (61.5%). This agrees with the findings of Adigwe et al, [7] and Oti et al, [20] . The reason for this could be due to the fact that men are usually more adventurous than females and are more likely to develop the risk factors of stroke such as hypertension, diabetes, smoking etc.…”
Section: Ijmsdh (2024)supporting
confidence: 94%
See 3 more Smart Citations
“…The result of this study also revealed that majority of the stroke cases seen at the neurology clinic of physiotherapy department UPTH were male 208 (61.5%). This agrees with the findings of Adigwe et al, [7] and Oti et al, [20] . The reason for this could be due to the fact that men are usually more adventurous than females and are more likely to develop the risk factors of stroke such as hypertension, diabetes, smoking etc.…”
Section: Ijmsdh (2024)supporting
confidence: 94%
“…The case fatality in Africa averages about 35% but could be as low as 14.9% or as high as 77% when stroke is due to cerebral haemorrhage [5,6] . According to Adigwe et al, [7] , the prevalence of stroke in Nigeria is 1.14 per 1000 persons and a 30-day case fatality rate of 40%, and males more affected (males: female = 1.5:1). In Nigeria, stroke is a major cause of neurological admissions and its incidence has been on the increase due to rise in the incidence and prevalence of hypertension and diabetes [8,9] .…”
Section: International Journal Of Medical Science and Dental Health (...mentioning
confidence: 99%
See 2 more Smart Citations